Novel ubiquitination-related biomarkers for Crohn’s disease identified by multi-omics study and experimental validation - Hu, Jia; Nie, Kai; Wang, Xiaoyan (Frontiers in Immunology, 2025)
BackgroundUbiquitination plays a critical role in the onset and progression of Crohn’s disease (CD). Nevertheless, the role of ubiquitination-related genes (URGs) in CD remains incompletely characterized. This study aimed to identify URGs with diagnostic value in patients with CD and construct a URGs-based diagnostic model for CD.MethodsSingle-cell and bulk RNA sequencing datasets related to CD were retrieved from the Gene Expression Omnibus (GEO) database. Single-cell analysis was conducted to characterize cell subsets associated with ubiquitination processes. CellChat was employed to elucidate potential intercellular communication networks, providing insights into the signaling interactions among different cell subsets. Furthermore, High-dimensional weighted gene co-expression network analysis (hdWGCNA) was performed to identify gene modules significantly correlated with ubiquitination. To screen for ubiquitination-related genes with diagnostic potential, we integrated genes from the identified hdWGCNA modules with differentially expressed genes (DEGs) between CD patients and healthy controls. Subsequently, XGBoost was utilized to further refine and identify core genes. These core genes were then used to construct a gene-based diagnostic model for CD. Finally, the expression levels of the core genes were experimentally validated in both in vitro cell models and human tissue biopsy specimens.ResultsWe identified IFITM3, PSMB9, and TAP1 as core ubiquitination-related genes in CD patients. The diagnostic model constructed based on these core genes showed remarkable accuracy, with the area under the curve consistently exceeding 0.9. Three core genes correlated significantly with activated immune cells in the inflammatory microenvironment and showed positive correlations with immune checkpoints like CD40, CD80, and CD274. Levels of IFITM3, PSMB9, and TAP1 were significantly elevated in LPS and INF-γ-induced THP-1 cells. Elevated expression of TAP1 and PSMB9 was also confirmed in tissue biopsy specimens, demonstrating the potential of these genes as diagnostic biomarkers.ConclusionUbiquitination-related genes IFITM3, PSMB9, and TAP1 are diagnostic markers for CD. The model based on these three genes offers valuable insights for disease diagnosis and treatment, which facilitates clinical decision-making.